Motivation as the Link: Mediating Effects of Intrinsic and Extrinsic Drives on Student Success - Habiba Gulzar (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: Drawing on self-determination theory, this study aims to explore the student teacher relationship impact on the sense of belonging and academic engagement, as well as mediating effect of intrinsic and extrinsic motivation and moderating effect of perceived social support among university students of Malaysia. Methodology: The study employs a statewide survey approach, and data is gathered via online questionnaires utilising convenience sampling techniques from undergraduate students enrolled in various programs in public university in Malaysia. However, 500 final responses were regarded as legitimate data while PLS-SEM was used to analyze the data. Findings: The study reveals that intrinsic motivation mediates the relationship among student-teacher and sense of belongings. The findings also shows that extrinsic motivation mediates the relationship among student-teacher and academic engagement. The moderating effect of perceived social support with intrinsic and extrinsic motivation on sense of belongings and academic engagement was confirmed. Implications/Novel Contribution: By presenting intrinsic and extrinsic motivation as mediators in connection to academic engagement and a sense of belonging, this study has bridged the gap as well as broadened both the theoretical and empirical understanding. Finally, this study offers several key policy insights for policy makers and education leaders as well as future research agenda for education and social science researchers.